Overview of innovation capability assessment methods in the world and application to SMEs in Vietnam - Nguyen Quoc Hung; Tran Vu Tuan Phan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
Innovation in recent years is no longer a novel term, it has a strong impact on all subjects of developed or developing economies and societies. Research on innovation in general and enterprise’s innovation capability in particular is very necessary and there have been many different studies in the world. However, the assessment methods to suit the Vietnamese context is very lacking and faces certain difficulties. This article is conducted with the aim of synthesizing a number of outstanding innovative capability assessment methods in the world, the current status of application of some methods in Vietnam for small and medium enterprises (SMEs), from that we propose some suggestions for building innovative capability assessment methods for SMEs based on the analysis, comparison and comments of the authors. The results of this study will serve as a basis for further studies and an initial suggestion for the development of an appropriate method to assess innovation capability for SMEs in Vietnam in the coming time. Keywords: . Code: 23021002